The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1ce00455g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pulling, crystal and crucible rotation rate on the thermal stress and the melt–crystal interface in the Czochralski growth of germanium crystals

Abstract: The effect of the pulling rate on the melt–crystal interface shape and melt streamline is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that under stable melt flow structure conditions, the concavity of c-m interface increases continuously in the TSLAG crystal growth process. Moreover, for the same crystal height, a higher crystal rotation speed leads to a greater concavity of the c-m interface, which has been reported in studies on Cz crystal growth [17,18].…”
Section: Interface Shapesupporting
confidence: 67%
“…Therefore, it can be concluded that under stable melt flow structure conditions, the concavity of c-m interface increases continuously in the TSLAG crystal growth process. Moreover, for the same crystal height, a higher crystal rotation speed leads to a greater concavity of the c-m interface, which has been reported in studies on Cz crystal growth [17,18].…”
Section: Interface Shapesupporting
confidence: 67%
“…The temperature and flow fields in the elements of a growth furnace result from the coupling of several heat transfer modes, namely, conduction in all furnace parts, convection in the melt and growth atmosphere, and radiation inside the semitransparent crystal and between the furnace elements. [16][17][18][19][20][21] Radiative heat transfer plays a key role in the growth process, and it acts directly on the temperature gradients and thermal stress in the crystal influencing then its quality.…”
Section: Introductionmentioning
confidence: 99%